2024
DOI: 10.1039/d3cp05295h
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and optical properties of core–shell InAlN nanorods: a comparative study via LDA, LDA-1/2, mBJ, HSE06, G0W0 and BSE methods

Ronaldo Rodrigues Pela,
Ching-Lien Hsiao,
Lars Hultman
et al.

Abstract: Currently, self-induced InAlN core-shell nanorods enjoy an advanced stage of accumulation of experimental data from their growth and characterization as well as a comprehensive understanding of their formation mechanism by...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 117 publications
0
4
0
Order By: Relevance
“…To get more attractive results, the DFT techniques have been exploited with the GGA+ TB-mBJ approximation in order to obtain an estimated value of the electronic band gap energies. It is noted in passing that more precise bandgaps might be obtained using the Heyd Scuseria Ernzerhof (HSE06) hybrid functional for investigating the electronic and the optical properties of such compounds [40]. However, it has been remarked that these techniques have been explored in other numerical codes including quantum espresso rather than the Wien2k software simulating one.…”
Section: Resultsmentioning
confidence: 99%
“…To get more attractive results, the DFT techniques have been exploited with the GGA+ TB-mBJ approximation in order to obtain an estimated value of the electronic band gap energies. It is noted in passing that more precise bandgaps might be obtained using the Heyd Scuseria Ernzerhof (HSE06) hybrid functional for investigating the electronic and the optical properties of such compounds [40]. However, it has been remarked that these techniques have been explored in other numerical codes including quantum espresso rather than the Wien2k software simulating one.…”
Section: Resultsmentioning
confidence: 99%
“…Except where explicitly stated, the calculation setup adopted in this work is the one of the density-functional theory (DFT) within its Generalized Gradient Approximation (GGA) at the Perdew–Burke–Ernzerhof (PBE) level of theory as implemented in the Quantum Espresso code, , which employs plane-wave basis sets and projector augmented wave method (PAW) pseudopotentials. The methodology chosen for this work takes into account a recent comparative study of different levels of theory and their performance in terms of accuracy and efficiency in the specific context of the core–shell InAlN NRs …”
Section: Methodology and Computational Detailsmentioning
confidence: 99%
“…14,15 Nowadays, rapid advancements in various fields are driven by the continuous discovery of new materials and advancements in manufacturing methods. 16,17 Existing studies have demonstrated that methods such as the transfer matrix method, 18 rigorous coupled wave analysis 19 and the finite element method 20 are reliable for accurately calculating the radiation performance of emitters. Furthermore, by leveraging physical mechanisms such as surface plasmon resonance, 21 photonic crystal effects 22 and Fabry–Perot resonance, 23 emitters can be optimized to approach ideal performance.…”
Section: Introductionmentioning
confidence: 99%